Beobachtungen zur Struktur von Amos 2,6-12 - Förg, Florian (Biblische Notizen, 2007)
Amos 2,6-11 shows a concentric structure. Each of the four transgressions of Israel (V.6c.7a.7bα.8) has its counterpart in the four acts of grace named in V.9.10a.b.11a. Many scholars consider V.10-12 as an addition, but the elaborate construction has not been perceived.